Misconceptions about evolution: a comparative study between undergraduate biology majors and graduate students - Leonardo Augusto Luvison Araújo (Investigações em Ensino de Ciências, 2020)
Challenges to evolution education are widely discussed in the academic literature. Four decades of research have revealed a surprisingly high prevalence of misconceptions about evolution among students at all levels. Considering the relevance of this theme, this paper aims to compare the presence of misconceptions about evolution among Brazilian biology students at different study levels: beginner and advanced undergraduate students and at the post-graduation level. A research questionnaire with statements that express misconceptions about evolution was developed and validated, being applied in two editions of an extension course attended by students from different public and private universities. 46 responses from beginner undergraduate biology students, 42 responses from advanced undergraduates, and 34 responses from post-graduate students were obtained, totaling 122 completed questionnaires. The comparative analysis indicated an average reduction in misconceptions according to the progress in the academic formation of students. Significant differences between undergraduate and graduate students were found in some items, with the post-graduation group presenting a lower frequency of misconceptions about natural selection and adaptation. However, even in these questions, there is a high percentage of agreement in all groups. Together, the data discussed here indicate the need for special attention regarding the misconceptions related to natural selection, adaptation, and interpretation of phylogenies in the education of teachers, biologists, and even graduate students.